Physiological and Multi-Omics Approaches for Explaining Drought Stress Tolerance and Supporting Sustainable Production of Rice - Zargar, Sajad Majeed; Mir, Rakeeb Ahmad; Ebinezer, Leonard Barnabas; Masi, Antonio; Hami, Ammarah; Manzoor, Madhiya; Salgotra, Romesh K.; Sofi, Najeebul Rehman; Mushtaq, Roohi; Rohila, Jai Singh; Rakwal, Randeep (Frontiers in Plant Science, 2022)
Drought differs from other natural disasters in several respects, largely because of the complexity of a crop’s response to it and also because we have the least understanding of a crop’s inductive mechanism for addressing drought tolerance among all abiotic stressors. Overall, growth and productivity of crops at a global level is now an issue that is more severe and arises more frequently due to climatic change-induced drought stress. Among the major crops, rice is a frontline staple cereal crop of the developing world and is critical to sustaining populations on a daily basis. Worldwide, many studies have reported a reduction in rice productivity over the years as a consequence of drought. Plants are evolutionarily primed to withstand a substantial number of environmental cues by undergoing a wide range of changes at molecular level, which involve gene, protein and metabolite interactions to protect the growing plant. Previously, these molecules were studied individually over years to understand a particular response and the underlying mechanisms. Currently, an in-depth, precise and systemic understanding of fundamental biological and cellular mechanisms activated by crop plants during stress is accomplished by an umbrella of -omics technologies, such as transcriptomics, metabolomics and proteomics. This combination of multi-omics approaches provides a comprehensive understanding of cellular dynamics during drought or other stress conditions in comparison to a single -omics approach. Multi-omics approaches can further pave the way to designing better diagnostics to overcome plant stresses, including drought. These approaches have led researchers to decipher those molecular chaperones and a well-coordinated ABA signaling pathway that play pivotal roles in regulating and responding to the effects of drought. Therefore, there is a greater need to explore and utilize information (big -omics data) from various molecular pathways to develop drought-resilient crop varieties for cultivation in ever-changing climatic conditions. The authors present research performed on similar aspects and voice their opinion based on omics-based technologies toward developing drought-resilient rice varieties. This review is focused on assembling current peer-reviewed published knowledge on the use of multi-omics approaches toward expediting the development of drought-tolerant rice plants for sustainable rice production and realizing global food security.